Effects of storage time and temperature on coagulation factor and natural anticoagulant activities in healthy individuals - Ryosuke Nakanishi; Tasuku Sakayori; Daichi Matsui; Mai Kono; Minase Maki; Claire Dunois; Yutaka Komiyama; Hiromi Morisaki (Scientific Reports)
Abstract Coagulation test results are influenced by many pre-analytical variables, including clinical sample storage conditions. This study investigated the effects of storage time and temperature on coagulation factor (FII, FV, FVII, FX, FVIII, FIX, FXI, FXII, and FXIII) and natural anticoagulant (antithrombin, protein C, and free protein S) activities. Blood samples were collected from 78 healthy individuals, and 3 samples were used for each coagulation factor and natural anticoagulant. Plasma was tested after centrifugation and storage at room temperature (18 to 25 °C) or refrigerated (2 to 8 °C) for 2, 3, 4, and 5 h, or frozen (− 15 to − 25 °C) for 1, 2, 3, and 4 months. For all storage conditions, the mean percentage change from baseline in evaluated activities was < 15%, except for FV and FVIII. For FV activities after frozen storage at − 15 to − 25 °C and FVIII activities at all storage conditions, the mean percentage change was > 15%. For FV and FVIII activities, the mean percentage change was < 15% after frozen storage at − 75 to − 85 °C for 1, 2, 3, and 4 months. To ensure appropriate clinical testing results, especially for FV and FVIII activity, storage condition and time should be critically controlled.